Maternal serum CA-125 repeated measurement during pregnancy and how to use as a prognostic factor of first trimester pregnancy outcome - Badr, Nesreen S.; El Mallah, Samira Y.; El Mahdy, Magda I.; Ahmad, Hanaa F. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The aim of this study was to estimate the prognostic efficacy of repeated measurement of maternal serum CA125 in first trimester threatened miscarriage. Methods: Prospective case control study was conducted in the outpatient clinic. 100 pregnant women were divided into 50 women with normal course of pregnancy, and the other 50 were subdivided into 25 pregnant women with lower abdominal pain without vaginal bleeding and 25 presented with minimal vaginal bleeding. Repeated measuring of serum CA125 was done for each case on the 5th, 10th weeks of gestation. Results: Findings of this study suggested the possibility of using serum CA-125 for determining the prognosis of first trimester threatened miscarriage with cut-off value of CA125 38.25 U/ml on the 5th week of gestation and 53 U/ml on the 10th week of gestation in patients presented with pain only but in patients presented with minimal vaginal bleeding the cut-off value of CA125 on the 5th week of gestation become 45.6 U/ml and 68 U/ml on the 10th week of gestation. Conclusions: CA125, on its own, can discriminate between continued and non-continued pregnancy.